Determinants of Islamic Banks's Profitability in Indonesia for 209-2013 - Paulin, Okky; Wiryono, Sudarso Kaderi (Journal of Business and Management, 2015)
Abstract – Performance efficiency of a bank being reliable to keeping trust and loyalty of clients. Banking performance can be seen from it profitability value, and as a result, financial ratios analysis in financial statement become an issue. This research focus on finding financial ratios that possible to be the profitability determinants of Islamic banks in Indonesia. Besides that, this research used quantitative analysis with CAMEL Method which consists of five aspects; there are capital, asset, management, earning, and liquidity. Independent variables that tested as the determinants of profitability are NPF, BOPO, NIM, FDR, PPAP Compliance, NPA, EA, and LIQD. In other side, dependent variable which represents bank’s profitability is ROA Through purposive sampling technique, selected 6 banks as samples that met with the criteria of 5 years observation period (2009 – 2013) from 11 population of Islamic banks in Indonesia. The samples data analyzed using SPSS and had passed classical assumption test and multiple linear regression to determine the regression model feasibility. Classical assumption tests that used are normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. While multiple linear regression shown in F-test and T-test. The result indicated that NPF, BOPO, NIM, FDR, PPAP Compliance, NPA, EA, and LIQD give significant effect simultaneously to ROA as profitability ratio of Islamic banks in Indonesia. Then partially, NIM and PPAP Compliance give significant positive effect to ROA, whereas BOPO has negatively significant influence to ROA. And other ratios, which are NPF, FDR, NPA, EA, and LIQD, have no significant effect on profitability of Islamic banks in Indonesia. Based on R-square value, the effect of those independent variables to ROA is 91.7%, so 8.3% residue is influenced by other variables outside this research. Based on that result, Islamic banks in Indonesia should increase the assets quality (PPAP Compliance), profit sharing income (NIM), and operational efficiency (BOPO). Its good for banks to give more focus on those area as an effort to gain public enthusiasm by showing the quality of banks with highest priority is BOPO by looking at it value which is 0.915. Second priority is NIM ratio, then third priority is PPAP Compliance ratio. Related to BOPO, bank management should validates every cost or expenses taken out by bank, whether it is necessary to issued or not. Related to NIM bank always calculates the cost of funds carefully so it can determines the competitive based profit sharing percentages. And related to PPAP Compliance ratio, bank management should observes the financing agreements that proper to be financed.Keywords: NPF (Non-Performing Financing), BOPO (Operational Efficiency), NIM (Net Interest Margin), FDR (Financing to Deposit Ratio), PPAP (Allowance for Earning Asset Possible Losses) Compliance, NPA (Non-Performing Asset), EA (Equity to Total Asset), LIQD (Liquid Asset to Total Deposit), ROA (Return On Asset), and profitability